33.2 Meänkieli i Sverige: Sammanfattning av en slutrapport i ELDIA-projektet - Arola, Laura
Abridged Swedish-language version of the report on the case study on the Meänkieli language in Sweden, conducted within the EU-FP7 research project ELDIA